Integrated Multi-Omics Analysis to Investigate the Molecular Mechanisms Underlying the Response of Auricularia heimuer to High-Temperature Stress - Fang Lu; Xin Sun; Xiaodong Dai; Piqi Zhang; Yinpeng Ma; Yafei Xu; Lei Wang; Jiechi Zhang (Journal of Fungi)
High-temperature stress is a key factor that reduces the yields of edible fungi. Auricularia heimuer (A. heimuer) is a nutrient-rich edible fungus that is widely cultivated in China. In this study, we analyzed the physiological, transcriptomic, and metabolomic results of A. heimuer (variety “Hei29”) under high-temperature stress. Our findings revealed that high temperatures (30 °C and 35 °C) significantly reduced hyphal growth, increased malondialdehyde content and antioxidant enzyme activity, and enhanced the accumulation of secondary metabolites, such as phenolic compounds and flavonoids. A total of 15 candidate genes potentially responsive to high-temperature stress were identified through transcriptomic analysis, including those involved in regulating antioxidant defense, heat shock response, sugar metabolism, amino acid metabolism, and accumulating secondary metabolites. Metabolomic analysis identified three candidate metabolites potentially responsive to high-temperature stress, including kinetin, flavonoids, and caffeic acid, as well as several metabolic pathways, including nucleotide metabolism, ABC transporters, and cofactor biosynthesis. These mechanisms help mitigate oxidative damage to cellular structures and energy deficits caused by elevated temperatures, enabling the fungus to maintain cellular stability, metabolic function, and growth under heat stress. This study is the first to explore the molecular mechanism of A. heimuer in response to high-temperature stress. The results provide valuable insights into the molecular mechanisms of heat stress tolerance in A. heimuer, highlighting potential targets for developing heat-tolerant strains for industrial application.